Socket Preservation Following Tooth Extraction Using Polylactide-Polyglycolide Acid Scaffold: Radiologic and Histologic Evaluation - ÖZKAN, YAŞAR (My University, 2024)
Purpose: To assess the healing process of the extraction socket and the dimensional changes that occur after alveolar ridge preservation utilizing a polylactide-co-glycolide scaffold (PLGA). Materials andMethods: The present study involved the extraction of 28 teeth from 14 patients. The total number of sockets was 28, which were divided into two groups consisting of 14 test sockets and 14 control sockets. The study group (SG) was subjected to socket preservation with a PLGA scaffold while the control group (CG) was left for spontaneous healing. The dimensions were measured before and after operation at 1, 3, and 5 mm below the alveolar crest horizontally and the height of buccolingual bone vertically. Results: According to the histologic analyses, the PLGA scaffold was resorbed within 4 months. CBCT imaging revealed a decrease in the horizontal crest dimension at three distinct coronoapical levels in SG, measuring 2.05 ± 1.05 mm at –1 mm, 1.51 ± 0.89 mm at –3 mm, and 0.92 ± 0.7 mm at –5 mm. CG showed readings of 1.22 ± 1 at –1 mm, 0.92 ± 0.67 at –3 mm, and 0.73 ± 0.69 at –5 mm. In comparison to CG, SG showed a significant reduction in horizontal losses at –1 mm. Vertical crest dimensions decreased by 1.64 ± 1.11 mm for the buccal bone height and by 1.56 ± 1.08 mm for lingual bone height in SG; in CG, the buccal and lingual bone height had mean values of 2.08 ± 1.44 mm and 1.73 ± 1.27 mm, respectively. There was no statistically significant difference observed in the vertical losses between the groups. Conclusions: Following a period of 4 months, the PLGA scaffold was completely resorbed. Based on CBCT measurements, horizontal resorption was lower than CG at –1 mm coronally.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Diş Hekimliği Oral Cerrahi Ve Tıp; Clinical Medicine (Med); Clinical Medicine; Dentistry Oral Surgery & Medicine; Ağız Cerrahisi; Oral Surgery; alveolar bone resorption; CBCT; polylactide-co-glycolide acid; socket preservation